PENINGKATAN SKOR TOEFL LISTENING COMPREHENSION TEST MELALUI PENGUATAN LISTENING SUB SKILLS (Sebuah Penelitian Tindakan Kelas) - Rohani, - (Universitas Negeri Semarang, 2010)
This study is an action research aiming at answering the question of:Ã‚Â Ã¢â‚¬Å“How thescore of the TOEFL Listening Comprehension Test of the students taking listeningcomprehension 1 in the even semester of 2006/2007 can be improved?Ã¢â‚¬ÂÃ‚Â Eighty fourstudents of three classes took part in the study. The data were collected through test,questionnaire, and field notes. The tests were used to measure the students' skill indoing the TOEFL listening comprehension test at the beginning of the research, afterthe first cycle, and at the end of the second cycle. The questionnaire was used to knowthe students' perception of the TOEFL listening comprehension test. The field noteswere used to record the students' responses and the effects of the treatment as a basis ofreflection. During the study, the skills of doing the TOEFL listening comprehensiontest were divided into 22 sub skills. There was a significant improvement at the end ofthe research. The pretest mean score of class A: 42.67, class B: 41.82, and class C:32.44. The mean score at the end of the first cycle of classA: 58.42, class B: 56.09, andclass C: 43.33. The mean score at the end of the second cycle of classA: 80.67, class B:80.67, and class C: 67.78. The percentage of the improvement of the mean score ofclass A: 52.89%, class B: 51.84%, and class C: 47.86%. A further detailed study isneeded to find a breakthrough in the method, technique, and material which will speedup the mastery ofTOEFLlistening comprehension test.Kata kunci: skor TOEFL, listening subskills, listening comprehension